The Efforts of School Principals in Improving the Pedagogical Competence of English Teachers in SMPN 1 Jeumpa - Munawwarah, Munawwarah; Efendi, Zuhri (Journal of Education Method and Learning Strategy, 2023)
Excellent education is largely determined by the ability and development of teachers in carrying out each learning task. Therefore, teachers need to have pedagogical competence so that the teaching and learning process can be carried out properly. This study aims to determine the efforts of school principals in improving the pedagogic competence of English teachers at SMPN 1 jeumpa. This study used a descriptive method with data collection techniques in the form of interviews and documentation methods, namely by interviewing school principals, vice principals, English teachers, and student representatives. While the data analysis technique used in this study uses data reduction, data presentation, and conclusion. From the results of the analysis, it can be concluded that the efforts of the school principal to improve the pedagogical competence of English teachers at SMPN 1 Jeumpa are carried out in several ways, namely: the school principal always provides training such as workshops, MGMP activities, and provides supervision. of all teachers. The principal also always provides motivation and appreciation to the teachers, and personal communication between the principal and the teacher, while the increase in teacher pedagogical competence at SMPN 1 Jeumpa has been fairly good.